A simulation-based analysis of variable flow pumping in ground source heat pump systems with different types of borehole heat exchangers: A case study. (1st January 2017) - Zarrella, Angelo; Emmi, Giuseppe; De Carli, Michele
Highlights: The work focuses on the variable flow in ground source heat pump systems. The constant and variable speed circulation pumps in the ground loop are compared. The constant temperature difference control across the heat pump is studied. The variable flow affects the energy performance of the heat pump. The constant temperature difference control offers an attractive energy saving. Abstract: A simulation model of ground source heat pump systems has been used to investigate to what extent a variable flow of the heat-carrier fluid of the ground loop affects the energy efficiency of the entire system. The model contemporaneously considers the borehole heat exchangers, the heat pump, the building load, and the control strategies for the circulation pumps of the ground loop. A constant speed of the circulation pumps of the ground loop was compared with a variable flow controlled by means of a constant temperature difference across the heat pump on the ground side considering the load profile of an office building located in North Italy. The analysis was carried out for a single U-tube, double U-tube and coaxial pipe heat exchangers. The control strategies adopted to manage the flow rate of the heat-carrier fluid of the ground loop affect both the heat exchange rate of the borehole field and the heat pump's long-term energy efficiency. The simulations show considerable differences in the system's seasonal energy efficiency. The constant speed of the circulation pumps leads to the best results as far as the heat pump's energy performance was concerned, but this advantage was lost because of the greater amount of electrical energy used by the circulation pumps; this, of course, affects the energy efficiency of the entire system. The optimal solution appears then to be a constant temperature difference in the heat-carrier fluid across the heat pump.